2016
DOI: 10.1186/s13148-016-0214-5
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 and the enigmatic organization of brain chromatin. Implications for depression and cocaine addiction

Abstract: Methyl CpG binding protein 2 (MeCP2) is a highly abundant chromosomal protein within the brain. It is hence not surprising that perturbations in its genome-wide distribution, and at particular loci within this tissue, can result in widespread neurological disorders that transcend the early implications of this protein in Rett syndrome (RTT). Yet, the details of its role and involvement in chromatin organization are still poorly understood. This paper focuses on what is known to date about all of this with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 165 publications
(214 reference statements)
0
30
0
Order By: Relevance
“…Interestingly, MBD is the only structured domain (α-helix) while 60% of MECP2 is unstructured [39]. There are several post translational modifications of MECP2 known which contribute to its multi-functional properties, phosphorylation, acetylation, SUMOylation, and ubiquitination [41]. …”
Section: Mecp2 Gene Transcript and Proteinmentioning
confidence: 99%
“…Interestingly, MBD is the only structured domain (α-helix) while 60% of MECP2 is unstructured [39]. There are several post translational modifications of MECP2 known which contribute to its multi-functional properties, phosphorylation, acetylation, SUMOylation, and ubiquitination [41]. …”
Section: Mecp2 Gene Transcript and Proteinmentioning
confidence: 99%
“…Methyl CpG binding protein 2 (MeCP2) is a basic DNA binding protein with preference for methylated DNA 1,2 and is highly abundant in the brain. 3 This protein functions as a transcriptional regulator by virtue of its interaction with both transcription activator and repressor complexes.…”
Section: Introductionmentioning
confidence: 99%
“…(C) Behavior: Although prolactin is most directly associated with lactation and some aspects of maternal behavior [128], the other pathways involved in prolactin release should also be considered when analyzing the effects of buprenorphine ( Figure 6E and Supplementary Materials Table S23). One of the key feedback pathways involved in prolactin release is dopamine release from the hypothalamus [130], as high dopamine levels exert an inhibitory effect on the release of prolactin [131]. The fact that buprenorphine can both increase or decrease prolactin levels supports the hypothesis that it interacts with the dopaminergic systems of the brain, and, also supporting this conclusion, it has been demonstrated that buprenorphine exposure affects the dopamine receptor density in the striatum [123].…”
Section: Buprenorphine: Opioidmentioning
confidence: 79%
“…Buprenorphine has also been suspected to act at an epigenetic level [147,148], as it has been linked with changes in gene expression of the methyl-DNA binding protein MeCP2, an important regulator of brain development, as well as several histone PTMs ( [131,149], Georgel's laboratory, unpublished data).…”
Section: Discussionmentioning
confidence: 99%